2002
DOI: 10.1021/jf020532u
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Aroma Compounds in Starch Matrices: Competitions between Aroma Compounds toward Amylose and Amylopectin

Abstract: The retention of three aroma compounds-isoamyl acetate, ethyl hexanoate, and linalool--from starch-containing model food matrices was measured by headspace analysis, under equilibrium conditions. We studied systems containing standard or waxy corn starch with one or two aroma compounds. The three studied aroma compounds interact differently: ethyl hexanoate and linalool form complexes with amylose, and isoamyl acetate cannot. However, in systems containing one aroma compound, we observed with both starches a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 12 publications
(17 reference statements)
2
45
0
Order By: Relevance
“…This was in part confirmed by Arvisenet et al (2002a), who demonstrated that corn starch retains ethyl hexanoate better than corn waxy starch. Savary et al (2007) showed that the distribution of aroma compounds depended mainly on the composition of the system, and that the nature of the aroma molecule did not have a great impact.…”
Section: Resultsmentioning
confidence: 64%
“…This was in part confirmed by Arvisenet et al (2002a), who demonstrated that corn starch retains ethyl hexanoate better than corn waxy starch. Savary et al (2007) showed that the distribution of aroma compounds depended mainly on the composition of the system, and that the nature of the aroma molecule did not have a great impact.…”
Section: Resultsmentioning
confidence: 64%
“…[41][42][43][44] The model-matrix chosen in our study is suitable to simulate the encapsulation and binding of hydrophobic compounds in native biological compartments present in vegetable tissues due to the presence of proteins, native lipids, and amylopectins. 45,46 SPME has been already successfully used for binding constant determinations in complex matrices, and is a technique that often reflects the molecular state of a biological system. 26,28,30 In line with our study objective, saturation of the system was again Testing of these three extraction modes was critical to understanding analyte behavior in complex matrices due to the various mass transfer mechanisms that drive the extraction process and the alteration of the analytes/matrix binding equilibria.…”
Section: Interestingly As Shown In Supporting Informationmentioning
confidence: 99%
“…In the presence of suitable guest molecules, the amylase of starch adopts a single helix formation that is stabilized by hydrogen bonds. 33,99,100 The outside surface of the single helix is hydrophilic while the inner surface of the helical channel is hydrophobic. These helices are suitable for accommodating hydrophobic guest molecules of appropriate dimensions.…”
Section: Helical Inclusion Complexesmentioning
confidence: 99%